Safe Conversion From Tacrolimus to Belatacept in High Immunologic Risk Kidney Transplant Recipients With Allograft Dysfunction. Issue 10 (18th May 2015) - Gupta, G.; Regmi, A.; Kumar, D.; Posner, S.; Posner, M. P.; Sharma, A.; Cotterell, A.; Bhati, C. S.; Kimball, P.; Massey, H. D.; King, A. L.
Abstract : There is no literature on the use of belatacept for sensitized patients or regrafts in kidney transplantation. We present our initial experience in high immunologic risk kidney transplant recipients who were converted from tacrolimus to belatacept for presumed acute calcineurin inhibitor (CNI) toxicity and/or interstitial fibrosis/tubular atrophy. Six (mean age = 40 years) patients were switched from tacrolimus to belatacept at a median of 4 months posttransplant. Renal function improved significantly from a peak mean estimated glomerular filtration rate (eGFR) of 23.8 ± 12.9 mL/min/1.73 m 2 prior to the switch to an eGFR of 42 ± 12.5 mL/min/1.73 m 2 (p = 0.03) at a mean follow‐up of 16.5 months postconversion. No new rejection episodes were diagnosed despite a prior history of rejection in 2/6 (33%) patients. Surveillance biopsies performed in 5/6 patients did not show subclinical rejection. No development of donor‐specific antibodies (DSA) was noted. In this preliminary investigation, we report improved kidney function without a concurrent increase in risk of rejection and DSA in six sensitized patients converted from tacrolimus to belatacept. Improvement in renal function was noted even in patients with chronic allograft fibrosis without evidence of acute CNI toxicity. Further studies with protocol biopsies are needed to ensure safety and wider applicability of this approach. Abstract : The authors report significant improvement in renal function in six high immunologic risk kidney transplant patients converted from tacrolimus to belatacept for allograft dysfunction, and they report a modified weaning protocol to minimize rejection risk.